Ethnic peculiarities of some indicators of metabolic and clinical status in infertile men - N. A. Kurashova (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
The article presents the results of the research of lipid peroxidation (LPO) and activity of components of antioxidant protection (AOP) in men of reproductive age with primary and secondary infertility, living on the territory of Buryatia and have abnormalities in spermogramme. Aim: to study the frequency structure of male infertility, the features of the system lipid peroxidation-antioxidant protection in men with normospermic and pathospermia Buryat and Russian nationality. A retrospective analysis was performed in 562 men of Russian and Buryat nationality, residing in the territory of the Republic of Buryatia. Study groups were as follows: 204 - Buryat, 358 - Russian. In this study we used clinical and laboratory methods and the statistical analysis of the obtained data. Study the contents of products of lipid peroxidation (LPO) and activity of components of the antioxidant protection (AOP) was studied in 113 infertile men (71 Buryat, 42 Russian). Group of infertile men were divided into a group with normospermia and pathospermia. High rate of male factor infertility in men of Russian and Buryat populations was found. No difference was found for frequency and structure of reproductive disorders in men depending on ethnicity. The frequency of male factor in infertile marriages and structure of the causes of male infertility and made comparisons based on ethnicity. Was found the presence of oxidative stress in patients with pathospermia. The findings suggest about the unfavorable pro-and antioxidant status of men with pathospermia, both Russian and Buryat populations. The differences indicate a different degree of activity of metabolic processes in infertile men of different ethnic groups.